Back to baselines: measuring change and sharing data - Förch, Wiebke; Kristjanson, Patti; Cramer, Laura; Barahona, Carlos; Thornton, Philip K. (BioMed Central, 2014)
International research for development is under increasing pressure to demonstrate development outcomes that enhance people’s food security and well-being while preserving the natural resource base. The CGIAR Research Programme on Climate Change, Agriculture and Food Security (CCAFS) integrates thematic research at several levels with multiple global, regional and local partners, with the aim of identifying and testing pro-poor adaptation and mitigation practices, technologies and policies for food systems, adaptive capacity and rural livelihoods. We describe a process to design and implement baselines across 2,095 households and 108 villages spread over 15 sites in 12 countries of West and East Africa and South Asia, and to archive, document and analyse the data and make them publicly available. We critically examine the process in relation to design, institutional arrangements, and partnerships. The process was long, complex and expensive. We share important lessons learned regarding how to obtain baseline data for rural populations in agricultural systems, as a basis for prioritising research and monitoring progress towards enhanced food security and increased household welfare, in part through uptake of sustainable changes in agricultural practices.
Keywords: Behavioural change; Partnership; Climate change; Food security; Africa; Asia; Livelihood; Survey methods